ANALISIS PEMANFAATAN AUTONOMOUS UNDERWATER VEHICLE (AUV) HUGIN 1000 GUNA MENDUKUNG OPERASI PUSHIDROSAL - Yogo Pratomo; Chiristian Lumban Tobing; Octav Bayu Dirgantara (Faculty of Science and Technology University of Pramita Indonesia, 2023)
The territory of the Unitary State of the Republic of Indonesia has sea waters that are wider than the land area, besides that the sea waters area has a wealth of diverse natural resources both in the fields of hydrography and oceanography. However, if faced with other threats originating from below the surface of the water, such as the Autonomous Underwater Vehicle (AUV), ships on the water will find it difficult to detect because the AUV has secrecy and intrusion properties that are difficult for opponents to detect. The Hugin 1000 Autonomous Underwater Vehicle has a navigation system and survey equipment system with acoustic wave transmission which is influenced by the physical properties of the water medium such as temperature and salinity. Every change in the physical properties of water is largely determined by the depth of the water column and its geographic location. The concept of winning a war at sea is that we are able to master the underwater battlefield to provide an advantage that can be used to defeat the opposing forces. The concept of underwater warfare is more complicated than warfare over water, because not only do we have to gain technological superiority from our opponents, but also knowledge and sufficient information about the characteristics of our own combat/operations mandala such as the completeness of hydrographic and oceanographic data. The development and advancement of technology in the field of underwater detection is so rapid that understanding the information dynamics of hydro-oceanographic parameters is one of the keys in determining the superiority of the battle. With good data in the form of hydrographic and oceanographic data, it will be easier to determine strategies in battle. The concept of underwater warfare is more complicated than warfare over water, because not only do we have to gain the advantage of the opponent's technology, but also knowledge and sufficient information about the characteristics of the combat/operational mandala itself, such as the completeness of hydro-oceanographic data.